Effect of GA3 on ripening and cell wall component metabolism of persimmon fruit - LUO Zi-sheng (浙江大学学报. 农业与生命科学版, 2006)
Effect of GA3 on the ripening and cell wall component metabolism of persimmon fruit (Diospyros kaki L. cv. Bianhua) was investigated after the fruit was treated with 50 mg·kg-1 GA3 for 10 minutes or not (control) at 20 ℃. Results showed that GA3 treatment not only significantly delayed the onset of ethylene production peaks and respiration climacteric in persimmon fruit, but also significantly retarded the activities of polygalacturonase (PG), pectinesterase (PE), β-galactosidase (β-Gal) and cellulase during storage. Consistent with the activity declining of cell wall hydrolase, GA3 treatment also delayed the depolymerization of propectin, cellulose and retarded the increasing of water soluble pectin (WSP) compared with the control fruit. The results suggest that application of GA3 can delay ripening and extend the postharvest life of persimmon fruit.